Pembaruan Fungsi Keuangan Perusahaan - Wintoro, Djoko (International Research Journal of Business Studies, 2008)
The finance functions have experienced evolutionary renewal. However, these events have not yet studied intensively. This study explores the ability of companies to perform new finance function as a business partnership function which focus on stock market communication. While this is an important evolving function, the study found that listed companies in Indonesian Stock Exchange have not performed the ability well enough yet. The study uses data from Indonesian Stock Exchange for the period 2006-2007. On average, investors did not give significant reward to information about the growth performance of the corresponding listed companies. The author suggests that a renewal of finance function of Indonesian companies is required.